(untitled) (Journal of Science and Technology, 2016)
This paper reviews a set of key issues arising in the context of the prospective monetary integration of West African countries into a single currency zone. It examines the economic arguments relating to the timing of a future adoption of a single currency by the West African states. In doing so, the analysis pertains to the prospects for meeting the convergence criteria set in a sustainable manner, particularly highlighting on the, contemporary parameters that can be considered instrumental in the strategic decision to introduce a single currency in the sub-region. The paper concludes that, on balance, if the intermediate arrangements, such as the convergence criteria set and the establishment of independent supranational central Bank work out well, then complete economic integration of the sort as envisaged in the original ECOWAS treaty could possibly ensue. However, looked at from the perspective of the West African economies, as relatively weak with fragile structures and almost all these countries depend on donor funds to finance their budgets, the risk that member states of Eco could turn inward in a way that is destructive of the monetary union is quite real and hence limits the success of monetary integration in the sub-region. This means that participating member states must work diligently to achieve a high degree of sustainable convergence in terms of low inflation and sound public finances. Macroeconomic policy surveillance and peer group pressure should follow provided guidelines and sufficient political will should override national short-term interest.